Dialectics of the sacred in Soviet visual propaganda of the 1920-60s - Egor Fedosov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2018)
A number of modern philosophers believe that Soviet ideology, despite materialism and atheism of Marxist doctrine, had noticeable spiritual and religious features. It would be interesting to try to substantiate this statement not only by philosophical and theoretical but also by historical facts. This article studies Soviet visual propaganda, namely posters and caricatures of the 1920–1960s that refl ect the evolution of Communist ideas in the clearest and most concentrated form. The main aim of the analysis is by means of this type of historical source to identify categories, images and symbols with religious connotation. The article identifi es themes in which these elements were present, the specifi city of their use in diff erent historical periods and their connection with other contexts in the Soviet propagandistic material. The study of visual propaganda confi rms that it did make use of the symbolism endowed with sacred meaning. Meanwhile, in the 1940–1950s such categories and images existed (at least in their Christian version) chiefl y beyond the atheist agenda. Their presence in posters and caricatures cannot be characterised as regular and frequent, however they reveal certain sequence, internal logic, and interconnection. Although the extent of religiosity of the Communist ideology should not be overestimated, the analysis generally shows that the Soviet worldview was rather complex and more varied than the Marxist theory implied, and many Soviet slogans and images need to be seen within a wider civilisational and spiritual context.